2021
DOI: 10.1111/ina.12913
|View full text |Cite
|
Sign up to set email alerts
|

Work productivity in the office and at home during the COVID‐19 pandemic: A cross‐sectional analysis of office workers in Japan

Abstract: Since 2020, the coronavirus disease 2019 (COVID-19) pandemic has threatened public health worldwide, and caused drastic changes to work styles and work environments. With regard to work style, COVID-19 has accelerated the recent trend to work from home (WFH). According to the International Labour Organization, only 7.9% of the world's workforce worked from home on a permanent basis prior to the COVID-19 pandemic. 1 As a result of government-imposed lockdowns and declarations of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
2
26
1
Order By: Relevance
“…The main result of this paper is that, in the case of WFH employees living in urban areas with housemates, HSWs in all types of residences had problems related to noise. This finding is different from that shown by Umishio et al (2021) [ 20 ], where satisfaction with the sound environment was higher at home than in the office. One possible reason for this is that, unlike the study by Umishio et al, this paper targeted only WFH employees living in urban areas with housemates.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The main result of this paper is that, in the case of WFH employees living in urban areas with housemates, HSWs in all types of residences had problems related to noise. This finding is different from that shown by Umishio et al (2021) [ 20 ], where satisfaction with the sound environment was higher at home than in the office. One possible reason for this is that, unlike the study by Umishio et al, this paper targeted only WFH employees living in urban areas with housemates.…”
Section: Discussioncontrasting
confidence: 99%
“…Umishio et al [ 20 ] conducted a questionnaire survey and environmental measurements on 916 WFH workers in 22 offices in Japan. The results showed that home workers were less satisfied with the lighting, spatial, and IT environments and more satisfied with the thermal, air, and sound environments compared to office workers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that WFH is implemented in many types of organizations (Pathak et al, 2021;Umishio et al, 2021). The dimension of WFH includes space, time, and social roles (Gądecki et al, 2018).…”
Section: Work From Homementioning
confidence: 99%
“…Numerous studies on productivity while working from home have been conducted, and they suggest that productivity, job satisfaction, and life satisfaction improves while working from home compared with working from the office [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. In a survey of call center employees of travel agencies, Bloom et al [ 15 ] showed that working from home improved productivity by 13%.…”
Section: Introductionmentioning
confidence: 99%